Aromatic Rice with Multiple Disease Resistance Developed through Anther Culture - Kharate, Pawankumar; Pusadkar, Pratik; Patel, Nirmala Bharti; Maurya, Shrinkhla; Jha, Zenu (International Journal of Bio-resource and Stress Management, 2021)
The experiments were conducted during kharif (June to September) 2018 and 2019 to screen 7 aromatic rice double haploid (DH) lines developed against Bacterial Leaf Bligh (BLB) and blast disease. Three genes Xa21, xa13, xa5 for BLB resistance and two genes Pi1, Pi2 for blast resistance was introgressed into a local aromatic rice variety Dubraj from Chhattisgarh State of India. Dubraj is extremely popular aromatic short medium grain variety in Chhattisgarh and Madhya Pradesh region and hence used in this study. RPBIO-226 and PR122 rice variety is used as donor for BLB and blast resistance respectively. 7 DH lines (L-1 to L-7) were developed from the crosses (Dubraj X RPBIO-226 X PR122) in the year 2017. Phenotypic evaluation for BLB diseases resistance has shown that L-1, L-6 and L-7 (score 1) has a similar resistance as the control check RPBIO-226(score-1) and 3 lines with moderate resistance (L-3 score 2) (L-4 score 3) (L-5 score 3). For blast disease, three lines (L-4, L-6 and L-7) were identified as resistance with the disease score of 1, whereas three were grouped under the section moderately resistant (L-1, L-3 and L- 5) with a disease score of 3. Sensory test (1.7% KOH) was conducted for the estimation of presence / absence of aroma. Moderately strong aroma was present in four lines (L-1, L-3, L-6 and L-7). On the basis of yield and presence of aroma in grain, L-3 has been selected with moderately resistant to BLB and blast for further advancement and subsequently evaluated under State Initial Evaluation Trial (SIET) during kharif 2020. Within 3 years of development of DH line, L-3 is under varietal developmental trail, which itself indicate the efficacy of anther culture in fixing homozygosity and speedy development of desired variety within short period of time.